Peningkatan Kinerja UMKM Perempuan: Literasi Keuangan, Pengelolaan Keuangan dan Kualitas Laporan Keuangan - Rahmawati R; Nur Vadila Putri (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The purpose of this research is to analyze the influence of financial literacy on financial management and the quality of financial reports; financial management on the quality of financial reports and the performance of women-led SMEs; the quality of financial reports on the performance of women-led SMEs; financial literacy on the performance of women-led SMEs through financial management and the quality of financial reports; and financial management on the performance of women-led SMEs through the quality of financial reports, specifically focusing on Women-led SMEs in the city of Parepare, South Sulawesi Province. The research design and approach employed in this study is a non-experimental design with a quantitative research approach. The location of this study is in the city of Parepare, South Sulawesi Province, with the population being all female Micro, Small, and Medium Enterprises (MSMEs) operators in Parepare. The total sample consists of 80 women-led MSMEs in Parepare. The data analysis technique involves path analysis using AMOS version 22 for data processing, along with the Sobel test. The research findings indicate that: 1) Financial literacy has a positive and significant influence on financial management, the quality of financial reports, and the performance of MSMEs. This implies that improved financial literacy enhances financial management, higher-quality financial reporting, and improved performance of women-led MSMEs. 2) Improved financial management significantly impacts the enhancement of the quality of financial reports and the performance of women-led MSMEs. 3) The quality of financial reports also has a positive and significant influence on the performance of women-led MSMEs. 4) Financial literacy indirectly has a positive and significant impact on the performance of women-led MSMEs mediated by financial management and the quality of financial reports. 5) Financial management also indirectly has a positive and significant impact on the performance of women-led MSMEs through the quality of financial reports.